Home Treatment for Acute Mental Disorders - Heath, David S. (Taylor & Francis, 2004)
In the U.S., when a patient is in need of rigorous psychiatric care, the first step is hospitalization. However, elsewhere in the world, psychiatric home treatment is proposed as an alternative. Model programs in Canada and the United Kingdom are publicly administered by community health agencies or teaching hospitals. Home Treatment for Acute Mental Disorders provides a review of the literature on home care and describes working programs around the world. This timely volume reviews treatment plans for different disorders with case illustrations, explains the administration of a PHC program and offers guidelines to case workers. It will be of interest to psychiatrists and policy makers working on the issue of patient hospitalization.